Oxysterols and redox signaling in the pathogenesis of non-alcoholic fatty liver disease. (November 2013) - Serviddio, G.; Blonda, M.; Bellanti, F.; Villani, R.; Iuliano, L.; Vendemiale, G.
Abstract Oxysterols are oxidized species of cholesterol coming from exogenous (e.g. dietary) and endogenous (in vivo) sources. They play critical roles in normal physiologic functions such as regulation of cellular cholesterol homeostasis. Most of biological effects are mediated by interaction with nuclear receptor LXRα, highly expressed in the liver as well as in many other tissues. Such interaction participates in the regulation of whole-body cholesterol metabolism, by acting as "lipid sensors". Moreover, it seems that oxysterols are also suspected to play key roles in several pathologies, including cardiovascular and inflammatory disease, cancer, and neurodegeneration. Growing evidence suggests that oxysterols may contribute to liver injury in non-alcoholic fatty liver disease. The present review focuses on the current status of knowledge on oxysterols' biological role, with an emphasis on LXR signaling and oxysterols' physiopathological relevance in NAFLD, suggesting new pharmacological development that needs to be addressed in the near future.